Bioactive compounds, associated health benefits and safety considerations of Moringa oleifera L.: an updated review. Issue 2 (28th May 2020) - Chhikara, Navnidhi; Kaur, Amolakdeep; Mann, Sandeep; Garg, M.K.; Sofi, Sajad Ahmad; Panghal, Anil
Abstract : Purpose: The purpose of this paper is to review the nutritional and phytochemical value of Moringa oleifera L., along with health benefits. Moringa oleifera, a highly valued plant grown throughout the world and all parts of tree used in different food formulations, possess industrial and therapeutic uses. This plant is gaining popularity because of its nutrient-rich root, leaves, flowers and fruits, having immense traditional medicinal uses and proved pharmacological properties. Design/methodology/approach: Major well-known bibliometric information sources such as Web of Science, Scopus, Mendeley and Google Scholar were searched with keywords such as nutrition value of Moringa oleifera, bioactive compounds, health benefits, processing and safety were chosen to obtain a database of 1, 386 papers. A final database of 70 scientific sources was made after sorting and classifying them according to different criteria based on topic relevance, country of origin and year of publication. Findings: The literature reflects that Moringa contains all necessary macro, micro-nutrients and bioactive compounds (terpenoids, polyphenols, flavonoids, glucosinolates, alkaloids, glycosides and carotenoids). Scientific studies illustrate that M. oleifera and its bioactive constituents could play a vital role in the prevention of several chronic and degenerative diseases associated with oxidation stress. The recent upsurge in consumer interest for health foods has opened up new vistas for plant products containing bioactive compounds in different food formulations. Originality/value: This paper highlights phytochemicals, pharmacological properties, bio-accessibility, food and industrial applications of Moringa. Moringa pods are traditionally preferred for enlarged liver and spleen, intestinal worms, weakness, neurological disorders and skin disease. A seed is natural and an inexpensive coagulant used to remove organic particles from water.